Modified delay compensation in demand response for frequency regulation of interconnected power systems integrated with renewable energy sources. Issue 1 (31st December 2022) - Bhuyan, Swetalina; Halder Nee Dey, Sunita; Paul, Subrata
Abstract: This paper puts forward a lead compensator- based PI controller for Demand Response (DR) loop which is included in the conventional Automatic Load Frequency Control (ALFC) model to improve the frequency control process of power system. Though DR is a good solution for ALFC but the vital problem in DR is the existence of communication delay between control centre and appliances. The proposed lead compensator can generate phase lead at the output of the DR loop to eliminate the adverse effects of the delay on the system performance. To verify the effectiveness of the proposed controller for ALFC problem, two different two- area transfer function models of power system are tested. At first the approach is analysed for a wind integrated two- area thermal power system, later the same is extended for a two- area hydrothermal system. The system dynamic performances in presence of proposed compensator are obtained with all the controllers tuned. The Particle Swarm Optimization (PSO) technique is used to tune all the controller parameters of the DR loop as well as the ALFC loop. The results demonstrate the usefulness of the proposed lead compensator in the event of communication delay and step load variation. Finally, the performance of lead compensator in DR exhibits robust performance even with the variation in disturbance parameters and operating conditions in the system